Foreign Policy and Ethnic Tensions in FYROM after the Greek-Skopje Interim Agreement - Sfetas, Spyridon (Études helléniques / Hellenic Studies, 1999)
The following article describes how the Greek-Skopje Interim Agreement brought about a noticeable improvement in bilateral relation s and interbalkan cooperation. The resulting climate facilitated FYROM’s integration into Europe, e.g. admission to certain European organizations, an agreement on co-operation with the European Union. Despite the name issue, Greek-Skopje relations are excellent. As a member of NATO and the European Union, Greece is not only diplomatically placed bat also economically developed and thus in a position to contribute to FYROM’s economic recovery and survival. Contrary to Bulgaria and Yugoslavia, Greece does not challenge the Slavomacedonian identity, created after 1944 to counteract Bulgarian and Serbian aspirations, as long as this new identity does not infringe upon the cultural heritage of Hellenism, or lay territorial claims of any kind on Greece. The Albanian factor in FYROM, a destabilizing force, brings Skopje closer to Athens, since Greece applies a policy of stabilization and regional security.